AB0702 Improvement of fatigue in patients with spondyloarthritis treated with anti-tnf therapy: a prospective study in a real-life setting. (15th June 2017) - Desouches, S; Gaigneux, E; Louati, K; Lemeunier, L; Beauvais, C; Sellam, J; Berenbaum, F
Abstract : Background: Besides randomized controlled trials evaluating biologic agents on fatigue, the impact of anti-TNF therapy on this crucial symptom has been poorly assessed in a real-life setting (1). Objectives: To assess the early effect of etanercept (ETN) on fatigue-related outcomes in spondyloarthritis (SpA) patients in a real-life setting. Methods: This prospective study included patients with active SpA fulfilling ASAS 2009 axial or peripheral criteria requiring an anti-TNF. All patients were treated with ETN 50mg weekly. BASDAI, BASFI, functional assessment of chronic illness therapy-fatigue (FACIT-F) (0 maximum and 52 the minimum of fatigue) and visual analogic scale of fatigue (VAS-F) (0 the minimum -100 maximum of fatigue) were assessed at inclusion at the time of ETN beginning (M0) and 4±1 months later (M4). The primary outcome was the M0-M4 change of VAS-F. The secondary outcomes were i) the M0-M4 change of FACIT-F ii) the frequency of patients who met improvement according to FACIT-F (defined as the minimal clinically important difference of FACIT-F corresponding to a 4-points decrease (FACIT-F responders). To determine whether fatigue change was related to disease activity improvement, a correlation between M0-M4 changes of BASDAI and VAS-F or FACIT-F was determined. Results: 30 SpA patients were enrolled (60% women, mean age ± standard deviation 39±8 years-old, axial SpA 83%, mean BMI 26±4, 80% ETN as a 1st line). Mean BASDAI improved at M4 (M0 48±20 versus M4 36.5±22; p=0.04) as well as VAS-F (M0 69±18 vs M4 52±24; p=0.01). The frequency of patients having VAS-F>50/100 was 86% at M0 and decreased at 36% at M4. Conversely, no significant change was observed concerning FACIT-F (M0 24.5±24 versus M4 28.8±11: p=0.36). At M4, 64% patients were FACIT-F responders. FACIT-F and VAS-F M0-M4 changes were highly correlated (r=0.78, p<0.0001). Despite no correlation between BASDAI and FACIT-F M0-M4 changes (r=0.36, p=0.1), a trend was observed for BASDAI and VAS-F M0-M4 changes in the same fashion (r=0.36, p=0.07). Interestingly, there was no baseline clinical characteristic associated with subsequent better fatigue improvement. Conclusions: This real-life study investigating the early effect of etanercept therapy on fatigue in SpA patients showed that fatigue (according to VAS-F) significantly improved while effect on FACIT-F was less pronounced. This improvement was explained, only in part, by disease activity improvement. References: Chauffier K, et al Clin Exp Rheumatol. 2013;31:864–70. Acknowledgements: Grant from Pfizer. Disclosure of Interest: None declared